DETERMINING THE RISK OF TRANSPORT HUB CAUSED BY RELEASE OF DANGEROUS SUBSTANCE IN THE NEIGHBOURHOOD (Perner's Contacts, 2018)
This article describes a methodology for determining the number of passengers in public transport hubs for assessing the risk of the hub in caused by release of dangerous substance in the neighbourhood. The number of passengers in the transport hub is determined by the number and occupancy of public transport vehicles serving the transport hub, the average waiting time for the transport link, the time to transfer and other influences. The methodology is validated at the selected transport hub for the release of the dangerous substance – ammonia. The procedure will enable to quantify the number of people at risk in the event of an accident and then justify the intervention of the integrated rescue system.
Keywords: transport hub, risk, dangerous substance